Preparation of the mesoporous structure of MCM-41 and the effect of some factors on the properties of the tissue structure - ابراهيم راهب; حسام الركاد; أيهم غندور (Latakia University Journal -Basic Sciences Series, 2022)
Four samples of the mesoporous structure MCM-41 were prepared by hydrothermal treatment method with a molar ratio of Silica:CTAB is 1: 0.5 with changing the two factors of treatment temperature and treatment time to study their effect on the properties of the tissue structure, Whereas, a decrease in the value of the specific surface area was observed from 874.0 m2/g to 709.4 m2/g at 100 °C with increasing treatment time from 5 to 8 days, As well as its decrease from 901.0 m2/g to 592.9 m2/g at 120 °C, The total pore volume also decreased from 0.628 ml/g to 0.550 ml/g at 100 °C with increasing treatment time from 5 to 8 days, As well as its decrease from 0.707 ml/g to a 0.441 ml/g at 120 °C, It was also found that these two factors do not affect the value of the radii and the percentage of fine porosity..